Chemically Accessible Hsp90 Inhibitor That Does Not Induce a Heat Shock Response - Koay, Yen Chin (American Chemical Society, 2014)
[Image: see text] Recent cancer therapies have focused on targeting biology networks through a single regulatory protein. Heat shock protein 90 (hsp90) is an ideal oncogenic target as it regulates over 400 client proteins and cochaperones. However, clinical inhibitors of hsp90 have had limited success; the primary reason being that they induce a heat shock response. We describe the synthesis and biological evaluation of a new hsp90 inhibitor, SM253. The previous generation on which SM253 is based (SM145) has poor overall synthetic yields, low solubility, and micromolar cytotoxicity. By comparison SM253 has relatively high overall yields, good aqueous solubility, and is more cytotoxic than its parent compound. Verification that hsp90 is SM253’s target was accomplished using pull-down and protein folding assays. SM253 is superior to both SM145 and the clinical candidate 17-AAG as it decreases proteins related to the heat shock response by 2-fold, versus a 2–4-fold increase observed when cells are treated with 17-AAG.